Few layer covalent organic frameworks with graphene sheets as cathode materials for lithium-ion batteries. Issue 12 (7th March 2019) - Wang, Zhaolei; Li, Yongjun; Liu, Pengju; Qi, Qiaoyan; Zhang, Fang; Lu, Guolin; Zhao, Xin; Huang, Xiaoyu
Abstract : Few layer COFs was incorporated with rGO to provide composite cathode materials with improved energy storage capability. Abstract : Covalent organic frameworks (COFs) have attracted increasing interest for their use as electrode materials for lithium-ion batteries (LIBs) by virtue of their microporous crystalline structures and robust networks. However, the tightly stacked bulk COFs and their intrinsic low conductivity inevitably result in an inefficient utilization of redox-active sites so as to lower the electrochemical performance. Herein, we proposed a general strategy to improve the energy storage capability of polyimide (PI)-COF based cathode materials, which included the decrease of their stacked layer numbers to a few layers via a mechanical milling method for the efficient utilization of redox-active sites and the incorporation of few-layer COF sheets with chemically reduced graphene oxide (rGO) to increase the charge transfer. The excellent electrochemical performance of the composite few-layer PI-COFs with rGO cathodes indicated that reducing the layer number of COFs and incorporating rGO may pave the way for the successful development of COF-based organic electrodes for LIBs.